Critical Review of the Book “English for the Students of Comparative Education: Primary and Preschool Education” - Vida Rahiminejad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Comparative Education is a research system, which helps the researcher to recognize the theoretical and practical background of two or more educational systems in different countries or regions. The aim of this kind of comparison is to analyze the similarities and differences between different educational systems in terms of organizational, structural, educational management, evaluation of training programs, and educational methods at different stages of education.Based on the general concept, comparative education compares all issues with regard to education in countries, and is considered as a course in MA and doctoral degree in European and American universities.There are different views towards the aims of comparative education. Borrowing other countries’ education model is not without a problem; however, paying attention to educational experiences of other countries can be beneficial in terms of choosing the best solution with regard to their own social characteristics.This book entitled “English for the Students of Comparative Education: Primary and Preschool Education” is not only an academic book, but also an educational textbook which includes the characteristics of teaching and learning concepts. Along with several positive points in this book, there are a few shortcomings pointed out, and some suggestions are provided to improve the textbook as well.